The Development and Demise of Child Labour in a Javanese Tea Plantation, 1900–2010 - Pujo Semedi; Gerben Nooteboom (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
Child labour used to be a common phenomenon in colonial tea plantations at the start of the 20th century. Since the 1970s, however, child labour started slowly to disappear from tea plantations on Java. In this article, we argue that the abolishment of child labour was never the result of improved legislation, but should be understood as part of several interrelated historical processes. Emerging educational opportunities for boys and girls, changes in labour demand, household strategies, diversification of family incomes, ideas on childhood, and technological changes in the production process are key to explain this change. This observation might raise serious considerations for policy makers today who aim to abolish child labour or improve working conditions of children.